Virtual vs traditional care settings for low-acuity urgent conditions: An economic analysis of cost and utilization using claims data. (January 2021) - Lovell, Tim; Albritton, Jordan; Dalto, Joe; Ledward, Cheryl; Daines, William
Background: On-demand, direct-to-consumer video (or virtual) visits represent one of the fastest growing telemedicine services. Due to the absence of an in-person physical examination, some question the effectiveness, efficiency and value of virtual care visits. To address these questions, we conducted a retrospective, cross-sectional review of Intermountain Healthcare's virtual care programme. Method: This study used SelectHealth claims for virtual, urgent, primary and emergency care delivered between 1 April 2016–31 March 2017. We included all claims with primary diagnosis from the nine most common categories for virtual care. A secondary data source included survey data indicating how virtual visits redirect care. Results: We matched 1531 virtual visit claims with claims from urgent (4377), primary (4388) and emergency care (2285). There were no differences in follow-up rates between virtual and urgent care and no differences in antibiotic use between virtual and urgent or primary care. Virtual care was significantly lower than all other care settings in utilization of laboratory and imaging services, index visit cost and total costs over 21 days. Conclusions: This study affirmed lower cost for virtual care without an associated increase in overall follow-up rates or antibiotic use when compared with urgent or primary care. This suggests that virtual visits are can be used to lower the total cost of care for applicable conditions. The implications are that virtual visits help lower operational costs of providing care, particularly in integrated systems with capitated reimbursement. Under the right circumstances, the increased adoption of virtual care should lead to greater savings.